Perancangan Jaringan Voice Over Internet Protocol (VOIP) Fakultas Teknik Universitas Riau - Putri, Veni Yuherlina; Sari, Linna Oktaviana; Anhar, Anhar (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2015)
This research discuss the designing of Voice over Internet Protocol (VoIP) in Engineering Faculty of Riau University. LAN of Engineering Faculty is connected through fast ethernet 100baseT cable and the backbone is connected through fiber optic. The project is designed using OPNET Modeler 14.5 Educational Version which consist of two skenario, VoIP network without router and with router. In the VoIP network with router, the network performance is measured by First-In-First-Out Queuing (FQ), Priority Queuing (PQ) and Weighted Fair Queuing (WFQ). The results showed that the value of MOS network with router (4.1 ) is more steadier than the network without router. The best performance of voice application is found in the routerand PQ network, where packet delay, jitter and Mean Opinion Score (MOS) are 330 ms, 0.9 ms, 4.1 respectively. Furthermore the best performance of video conference application is found in the same network where packet delay and jitter are 0.6 secondsand 0.2 seconds.Keywords :VoIP, network, Packet Queuing